The project-space model: enhancing sensemaking. Issue 1 (4th January 2017) - van der Hoorn, Bronte; Whitty, Stephen Jonathan
Abstract : Purpose: The purpose of this paper is to propose the project-space model as positively influencing sensemaking in the project context. There is currently minimal discussion of the tools used by project managers, teams and stakeholders to build their map of the project terrain or to make sense of a project's status. However, such sensemaking is critical to ongoing decision making and aligning action in any project. Design/methodology/approach: This paper uses framework analysis to examine the results of a completed action research case study that utilised a tool: the project-space model. Three frameworks are then utilised as an investigative lens to examine how the project-space model influenced sensemaking. Findings: The project-space model is found to enhance sensemaking within the case study. Specifically, its visual nature, the focus it brings to the plurality of experience and the need for plausibility rather than precision in understanding. Research limitations/implications: The findings are based on a single case study. Further studies could be undertaken to confirm extensibility. Practical implications: The project-space model is identified as having a favourable impact on sensemaking in the case study project. There is a need to consider what other tools are currently used or could be used by project teams to enhance sensemaking. Originality/value: Empirical, contextualised case study research highlighting the value of the project-space model as a sensemaking tool. Contribution to evidence on the efficacy of the project-space model as a useful tool for project managers.